Nephrotoxicity of ibandronate and zoledronate in Wistar rats with normal renal function and after unilateral nephrectomy. (September 2015) - Bergner, R.; Siegrist, B.; Gretz, N.; Pohlmeyer-Esch, G.; Kränzlin, B.
Graphical abstract: Abstract: A previous animal study compared the nephrotoxic effect of ibandronate (IBN) and zoledronate (ZOL), but interpretation of these study results was limited because of the model of minimal nephrotoxic dosage with a dosage ratio of 1:3. The present study investigated the nephrotoxicity of ibandronate and zoledronate in a 1.5:1 dose ratio, as used in clinical practice and compared the nephrotoxicity in rats with normal and with mildly to moderately impaired renal function. We compared rats with normal renal function (SHAM) and with impaired renal function after unilateral nephrectomy (UNX), treated either with ibandronate 1.5 mg/kg, zoledronate 1 mg/kg or placebo once (1×) or nine (9×) times. Renal function and markers of tubular toxicity were measured over a 27 week period. After last bisphosphonate treatment the rats were sacrificed and kidneys examined histologically. All bisphosphonate treated animals showed a significant tubular toxicity, which was temporary except in the ZOL-UNX-9×-group. Also the renal function was only transiently reduced except in the ZOL-UNX-9×-group. Histologically, bisphosphonate treatment led to cortical tubuloepithelial degeneration/necrosis and medullary tubuloepithelial swelling which were slightly more pronounced in ibandronate treated animals, when compared to zoledronate treated animals, especially with impaired renal function. In contrast to the previous study we found a similar nephrotoxicity of ibandronate and zoledronate in rats with normal renal function. In rats with impaired renal function the peak of toxicity had not even been fully reached until end of experiment in the zoledronate treated animals. The peak of toxicity seems to be more severe and delayed in rats with impaired renal function compared with rats with normal renal function.